Immobilized alkali-free deodorization catalyst and preparation method thereof
By combining cobalt phthalocyanine with mesoporous molecular sieve, a solid-supported alkali-free deodorizing catalyst is formed, which solves the problem of easy shedding and inactivation of active components in the prior art, improves the stability and service life of the catalyst, and reduces operation Cost and environmental pressure.
Patent Information
- Application Number
- CN202310720216.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-06-18
AI Technical Summary
When existing catalysts remove thiols from light hydrocarbons under alkali-free conditions, the active components are prone to shedding and inactivated, resulting in poor catalyst stability and increasing operating costs and environmental protection pressure.
Using a solid-supported alkali-free deodorizing catalyst, the Co-molecular sieve structure is formed by combining cobalt phthalocyanine with suitable microporous or mesoporous molecular sieve by in-situ synthesis method, and the active components and the carrier are connected through chemical bonds to reduce shedding and coalescence. Phenomenon.
It improves the stability of the catalyst, reduces operating costs, solves the problem of waste alkali liquid emission, and extends the service life of the catalyst.
Smart Images

Figure BDA0004291140860000081 
Figure BDA0004291140860000082 
Figure BDA0004291140860000091
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst suitable for alkali-free deodorization of light hydrocarbons or gasoline fractions and a preparation method thereof, and in particular to a solid-supported catalyst used in an alkali-free deodorization process and a preparation method thereof. Background Art
[0002] Light hydrocarbons produced in oil fields or refineries contain a large number of mercaptan components, such as CH3SH, C2H5SH, etc. In the context of increasingly stringent environmental legislation and deep utilization of light hydrocarbons, it is necessary to remove these sulfur-containing components. The technology of desulfurization of liquefied gas was first proposed by UOP in 1958, and has developed into a mature extraction and oxidation regeneration process. The most widely used technology is the Merox desulfurization technology of UOP in the United States and the fiber-film contactor alkali treatment technology of Merichem Co. in the United States. The technical principle is that strong alkali and mercaptan react to form sodium mercaptide, which is then oxidized to form disulfide substances under the action of phthalocyanine catalysts, and finally separated. The disadvantages of this method are: phthalocyanine cobalt catalysts are in the alkaline phase, easy to aggregate and deactivate, resulting in frequent catalyst replacement, and the catalyst cost is quite high; and the process requires continuous discharge of waste alkali liquid to meet the process index requirements, which increases operating costs and aggravates environmental pressure.
[0003] In order to solve the above problems, UOP proposed a fixed bed desulfurization process, the core of which is to disperse the phthalocyanine catalyst on a porous carrier and load it in a fixed bed. The mercaptan-containing hydrocarbon flows through the fixed bed to undergo oxidation reaction and remove mercaptan. US Patent USP2988500 discloses a supported cobalt phthalocyanine catalyst, which loads cobalt phthalocyanine on activated carbon and catalyzes the oxidation of mercaptan under the action of a soluble alkaline reagent. US Patent USP 5286372 loads a metal complex on a solid base, and no alkali solution is required when using this catalyst. Chinese Patent CN1200958A discloses a catalyst with a complex loaded on the surface of a solid alkaline oxide, which is formed by a sulfonate phthalocyanine cobalt or a carboxylate phthalocyanine cobalt with a negative ion group and a quaternary ammonium phthalocyanine cobalt with a positive ion group. The catalyst does not require an alkali solution during oxidation reaction, and its activity and stability are improved to a certain extent. Chinese patent CN 104588097A discloses a method for preparing a supported phthalocyanine catalyst, which comprises spraying a solution of metal phthalocyanine, a dispersant, an alkaline substance and water on a porous carrier, and achieving the purpose of highly dispersing and supporting the active component by dissolving the metal phthalocyanine.
[0004] At present, the preparation of this type of catalyst mostly adopts the method of loading (the preparation method in the above patents). Although the catalyst prepared by the loading method has high activity, since the carrier and the metal phthalocyanine compound are connected only by physical adsorption, the active components are very easy to fall off during the reaction and flow out of the reaction bed with the process flow, resulting in catalyst deactivation. Summary of the invention
[0005] Based on the problems existing in the prior art, the present invention provides a solid-supported alkali-free deodorization catalyst and a preparation method thereof. The catalyst can remove thiols from light hydrocarbons under alkali-free conditions, and the active component is bonded to the carrier by bonding, which is not easy to fall off and deactivate during the reaction process, greatly improving the catalyst stability and reducing the operating cost.
[0006] According to a first aspect of the present invention, the present invention provides a solid-supported alkali-free deodorization catalyst.
[0007] The solid-supported alkali-free deodorizing catalyst of the present invention comprises, by weight, 35%-65% molecular sieve, 10%-55% xMO·yM'2O3, and 5%-25% cobalt phthalocyanine; wherein M is an element of Group ⅡA or ⅡB, M' is an element of Group ⅢA or Ⅷ, and x:y=0.5-30.
[0008] Furthermore, M is at least one divalent metal selected from Mg, Ca, Ba, and Zn, and M' is at least one trivalent metal selected from Al, Fe, Co, and Ni.
[0009] Furthermore, the conventional molecular sieve is selected from at least one of Y-type molecular sieve, X-type molecular sieve, MCM-41 molecular sieve, Al / MCM-48 molecular sieve, SBA-15 molecular sieve, etc. The silicon-aluminum molar ratio of the molecular sieve is generally 0.5-200, preferably 1-50.
[0010] Furthermore, the solid-supported alkali-free deodorization catalyst of the present invention comprises, by weight, 30%-75% of molecular sieve, preferably 40%-55%; 10%-55% of xMO·yM'2O3, preferably 20%-35%; and 5%-25% of cobalt phthalocyanine, preferably 10%-20%.
[0011] According to the second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned solid-supported alkali-free deodorization catalyst.
[0012] A method for preparing a solid-supported alkali-free deodorization catalyst comprises the following contents:
[0013] (1) Preparation containing M 2+ and M' 3+Add the molecular sieve into the mixed solution and stir evenly;
[0014] (2) reacting the molecular sieve suspension obtained in step (1) with a mixed solution containing NaOH and Na2CO3 or a weak alkaline solution under stirring for a period of time;
[0015] (3) The material obtained in step (2) is filtered, washed, dried and calcined to obtain a composite carrier;
[0016] (4) Prepare a cobalt salt solution and transfer Co 2+ Exchange onto the composite carrier obtained in step (3);
[0017] (5) The material obtained in step (4) is filtered and dried to obtain Co molecular sieve solid base;
[0018] (6) The Co molecular sieve solid base obtained in step (5) is added to a mixture of pyridine and nitrobenzene, and heated to 50-110° C. under stirring; then phthalonitrile is added, and the reaction is carried out at 150-300° C.;
[0019] (7) The material obtained in step (6) is filtered, washed and dried to obtain the solid-supported alkali-free deodorization catalyst.
[0020] Furthermore, the stirring time in step (1) is generally 10 min to 180 min, preferably 60 min to 120 min.
[0021] Furthermore, in the mixed solution of step (1), M is an element of Group IIA or Group IIB, and M' is an element of Group IIIA or Group VIII; preferably, M is at least one divalent metal selected from Mg, Ca, Ba, and Zn, and M' is at least one trivalent metal selected from Al, Fe, Co, and Ni. 2+ and M' 3+ The mixed solution can be a nitrate solution or a hydrochloride solution of M and M'. 2+ and M' 3+ The concentrations of the mixed solutions are generally 0.1 mol / L-saturation concentration and 0.02 mol / L-saturation concentration. 2+ and M' 3+ The molar ratio is generally 0.5-30.
[0022] Furthermore, in step (2), the molar ratio of NaOH to Na2CO3 in the mixed solution is 1:3 to 30:1. The weak alkali solution is selected from at least one of aqueous ammonia (dilute aqueous ammonia) and dimethylamine. When the pH value in step (2) is titrated to 9 to 10, stirring is stopped and the mixture is allowed to stand for 10 to 180 minutes, preferably 60 to 120 minutes.
[0023] Furthermore, the filtering, washing, drying and roasting in step (3) can adopt conventional operating conditions in the art. The roasting conditions are: the temperature is generally 400-900°C, preferably 500-800°C, the roasting time is 4-10h, preferably 6-8h. The heating rate is 3-20°C / min, preferably 5-10°C / min.
[0024] Furthermore, the cobalt salt solution in step (4) is selected from at least one of Co(NO3)2, Co(AC)2 or CoCl2 solution. The operating conditions of the ion exchange in step (4) are: the temperature is room temperature to 200°C, preferably 80 to 150°C, and the exchange time is 12 to 36 hours, preferably 18 to 26 hours.
[0025] Furthermore, the filtering, washing, drying and roasting in step (5) can adopt conventional operating conditions in the art and will not be described in detail here.
[0026] Furthermore, in the mixed solution of step (6), the concentration of pyridine is 0.1-0.5 mol / L. The heating temperature is 50-110° C., preferably 80-110° C. After adding phthalonitrile, the reaction temperature is adjusted to 110-300° C., preferably 150-220° C., and the reaction is continued for 0.5-3 h, preferably 1-2 h after adding phthalonitrile.
[0027] Furthermore, the filtering, washing and drying in step (7) are carried out according to conventional procedures in the art.
[0028] The solid-supported alkali-free deodorization catalyst provided by the present invention can catalyze the oxidation of mercaptans to generate disulfides under non-alkaline conditions, and compared with conventional processes, no alkali solution is consumed, which can fundamentally solve the environmental protection problem of waste alkali solution discharge. In addition, the catalyst combines cobalt phthalocyanine with mesoporous molecular sieves in a solid-supported manner, effectively reducing the aggregation and deactivation problem of the cobalt phthalocyanine catalyst.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The solid-supported alkali-free deodorization catalyst provided by the present invention selects a microporous or mesoporous molecular sieve with a suitable pore structure as a basic carrier, MO and M'2O3 are used as solid bases, and the active component cobalt phthalocyanine is solidified into the catalyst through in-situ synthesis. The active component is firmly bonded to the cobalt phthalocyanine and the carrier molecular sieve, and the active component is not easy to lose.
[0031] 2. In the catalyst preparation method provided by the present invention, the mesoporous molecular sieve is first impregnated with a mixed solution containing M(NO3)2 and M'(NO3)3, and then calcined to obtain a solid base to create an alkaline environment on the molecular sieve carrier, thereby reducing or even eliminating the consumption of alkali solution in the desulfurization process.
[0032] 3. The catalyst provided by the present invention forms a Co-molecular sieve structure through ion exchange, and forms cobalt phthalocyanine through an in-situ synthesis method. Compared with similar supported catalysts, cobalt phthalocyanine is combined with the molecular sieve through chemical bonds, and basically does not dissociate, fall off, or aggregate during the catalytic reaction, and does not produce a deactivation effect, so it has a longer service life. DETAILED DESCRIPTION
[0033] The following is a detailed description of the immobilized alkali-free desulfurization catalyst and its preparation method of the present invention in conjunction with specific examples. The percentages involved in the examples are all mass percentages unless otherwise specified.
[0034] Example 1
[0035] Mix and dissolve 105g Zn(NO3)2·6H2O and 20g Al(NO3)3·9H2O in 500mL deionized water. Add 22.8g SBA-15 molecular sieve (silicon-aluminum molar ratio is 30) and stir to make a suspension. Under constant stirring, add 1mol / L ammonia water and the above solution to the same reactor at the same time, control the pH value to 10, and stir the reaction at room temperature for 3h. After filtering, wash with deionized water to a pH value of 7, dry at 95℃, and place in a muffle furnace for calcination at 700℃ for 4h to obtain a catalyst composite carrier.
[0036] Prepare 0.2 mol / L Co(AC)2, take 27 mL of Co(AC)2 solution and slowly drop it into the reactor. Stir at room temperature for 2 hours, heat to 85℃ and keep for 12 hours, and cool the reactor to room temperature. Filter, wash with deionized water, and dry at 180℃ to obtain a Co molecular sieve solid base sample.
[0037] Add Co molecular sieve solid base sample to the reactor, add pyridine and nitrobenzene mixed solution (pyridine concentration 0.3 mol / L, mixed solution 33 mL), stir continuously, and heat to 100 ° C. Then add 7 g of phthalonitrile, heat to 175 ° C, and react for 3 hours. After the reaction is completed, cool naturally to room temperature, filter, wash with hot nitrobenzene, dilute hydrochloric acid, deionized water and methanol in turn, and dry to obtain a solid catalyst.
[0038] Example 2
[0039] Mix and dissolve 115gNi(NO3)2·6H2O and 20gAl(NO3)3·9H2O in 500mL deionized water. Add 33.5g HY molecular sieve (silicon-aluminum molar ratio is 2) and stir to make a suspension. Under constant stirring, add 1mol / L NaOH and Na2CO3 mixed solution (NaOH and Na2CO3 molar ratio is 1:1) and the above solution to the same reactor at the same time, control the pH value to 10, and stir the reaction at room temperature for 5h. After filtering, wash with deionized water to pH 7, dry at 80℃, and place in a muffle furnace for calcination at 650℃ for 8h to obtain a catalyst composite carrier.
[0040] Prepare 0.2 mol / L Co(AC)2, take 54 mL of solution and slowly add it to the reactor. Stir at room temperature for 2 hours, heat to 85℃ and keep for 20 hours, and cool the reactor to room temperature. Filter, wash with deionized water, and dry at 190℃ to obtain Co(Y) molecular sieve·solid base sample.
[0041] Add Co(Y) molecular sieve·solid base sample to the reactor, add pyridine and nitrobenzene mixed solution (pyridine concentration 0.3 mol / L, mixed solution 65 mL), stir continuously, and heat to 90°C. Then add 14 g of phthalonitrile, heat to 190°C, and react for 3 hours. After the reaction is completed, cool naturally to room temperature, filter, wash with hot nitrobenzene, dilute hydrochloric acid, deionized water and methanol in turn, and dry to obtain a supported catalyst.
[0042] Example 3
[0043] Mix and dissolve 58gMg(NO3)2·6H2O and 20gAl(NO3)3·9H2O in 300mL deionized water. Add 14.3g SBA-15 molecular sieve (silicon-aluminum molar ratio is 30) and stir to make a suspension. Under constant stirring, add 1mol / L ammonia water and the above solution to the same reactor at the same time, control the pH value to 10, and stir the reaction at room temperature for 4h. After filtering, wash with deionized water to a pH value of 7, dry at 90℃, and place in a muffle furnace for calcination at 700℃ for 5h to obtain a catalyst composite carrier.
[0044] Prepare 0.2 mol / L Co(NO3)2, take 27 mL of the solution and slowly drip it into the reactor. Stir at room temperature for 5 hours, heat to 120°C and keep for 24 hours, and cool the reactor to room temperature. Filter, wash with deionized water, and dry at 200°C to obtain a Co(Y) molecular sieve solid base sample.
[0045] Add Co molecular sieve solid base sample to the reactor, add pyridine and nitrobenzene mixed solution (pyridine concentration 0.3 mol / L, mixed solution 33 mL), stir continuously, and heat to 100 ° C. Then add 7 g of phthalonitrile, heat to 200 ° C, and react for 2 hours. After the reaction is completed, cool naturally to room temperature, filter, wash with hot nitrobenzene, dilute hydrochloric acid, deionized water and methanol in turn, and dry to obtain a solid catalyst.
[0046] Example 4
[0047] Mix and dissolve 56gMg(NO3)2·6H2O and 20gAl(NO3)3·9H2O in 300mL deionized water. Add 21.1g HY molecular sieve (silicon-aluminum molar ratio is 2) and stir to make a suspension. Under constant stirring, add 1mol / L NaOH and Na2CO3 mixed solution (NaOH and Na2CO3 molar ratio is 1:2) and the above solution to the same reactor at the same time, control the pH value to 10, and stir the reaction at room temperature for 4.5h. After filtering, wash with deionized water to pH 7, dry at 80℃, and place in a muffle furnace for calcination at 650℃ for 6h to obtain a catalyst composite carrier.
[0048] Prepare 0.2 mol / L CoCl2, take 55 mL of the solution and slowly drip it into the reactor. Stir at room temperature for 5 hours, heat to 120°C and keep for 28 hours, and cool the reactor to room temperature. Filter, wash with deionized water, and dry at 150°C to obtain a Co(Y) molecular sieve solid base sample.
[0049] Add Co(Y) molecular sieve·solid base sample to the reactor, add pyridine and nitrobenzene mixed solution (pyridine concentration 0.3 mol / L, mixed solution 66 mL), stir continuously, and heat to 100°C. Then add 15 g of phthalonitrile, heat to 195°C, and react for 1.6 hours. After the reaction is completed, cool naturally to room temperature, filter, wash with hot nitrobenzene, dilute hydrochloric acid, deionized water and methanol in turn, and dry to obtain a supported catalyst.
[0050] Example 5
[0051] Mix and dissolve 30gMg(NO3)2·6H2O and 8gAl(NO3)3·9H2O in 200mL deionized water. Add 17.1g HY molecular sieve (silicon-aluminum molar ratio is 2) and stir to make a suspension. Under constant stirring, add 0.5mol / L ammonia water and the above solution to the same reactor at the same time, control the pH value to 9, and stir the reaction at room temperature for 3h. After filtering, wash with deionized water to pH 7, dry at 100℃, and place in a muffle furnace at 500℃ for 8h to obtain a catalyst composite carrier.
[0052] Prepare 0.2 mol / L Co(AC)2, take 55 mL of the solution and slowly drip it into the reactor. Stir at room temperature for 2 hours, heat to 150℃ and keep for 18 hours, and cool the reactor to room temperature. Filter, wash with deionized water, and dry at 150℃ to obtain a Co(Y) molecular sieve solid base sample.
[0053] Add Co(Y) molecular sieve·solid base sample to the reactor, add pyridine and nitrobenzene mixed solution (pyridine concentration 0.3 mol / L, mixed solution 67 mL), stir continuously, and heat to 90°C. Then add 15 g of phthalonitrile, heat to 180°C, and react for 3 hours. After the reaction is completed, cool naturally to room temperature, filter, wash with hot nitrobenzene, dilute hydrochloric acid, deionized water and methanol in turn, and dry to obtain a supported catalyst.
[0054] Example 6
[0055] Mix and dissolve 5gCr(NO3)3·9H2O and 8gMg(NO3)2·9H2O in 200mL deionized water. Add 14.8gHY molecular sieve (silicon-aluminum molar ratio is 2) and stir to make a suspension. Under constant stirring, add 0.8mol / L ammonia water and the above solution to the same reactor at the same time, control the pH value to 11, and stir the reaction at room temperature for 4h. After filtering, wash with deionized water to pH 7, dry at 90℃, and place in a muffle furnace for calcination at 800℃ for 5h to obtain a catalyst composite carrier.
[0056] Prepare 0.2 mol / L Co(AC)2, take 55 mL of the solution and slowly drip it into the reactor. Stir at room temperature for 2 hours, heat to 110℃ and keep for 22 hours, and cool the reactor to room temperature. Filter, wash with deionized water, and dry at 190℃ to obtain a Co(Y) molecular sieve solid base sample.
[0057] Add Co(Y) molecular sieve·solid base sample to the reactor, add pyridine and nitrobenzene mixed solution (pyridine concentration 0.3 mol / L, mixed solution 66 mL), stir continuously, and heat to 90°C. Then add 14 g of phthalonitrile, heat to 110°C, and react for 3 hours. After the reaction is completed, cool naturally to room temperature, filter, wash with hot nitrobenzene, dilute hydrochloric acid, deionized water and methanol in turn, and dry to obtain a supported catalyst.
[0058] Comparative Example 1
[0059] The alkali-free desulfurization catalyst was prepared by the method disclosed in CN1200958A. The prepared catalyst comprises 60 wt% molecular sieve, 20% solid alkali and 20% cobalt phthalocyanine. The molecular sieve and solid alkali are the same as those in Example 5.
[0060] Comparative Example 2
[0061] The alkali-free desulfurization catalyst was prepared by the method disclosed in CN1978058A. The prepared catalyst comprises 65% molecular sieve, 10% solid base and 25% cobalt phthalocyanine. The molecular sieve and solid base are the same as those in Example 6.
[0062] Table 1 Catalyst composition (wt%)
[0063]
[0064] The catalysts prepared in Examples 1-6 and Comparative Examples 1-2 were subjected to a desulfurization evaluation experiment. The raw materials used in the experiment had a sulfur content of 12000 μg / g and a mercaptan sulfur content of 11500 μg / g. A fixed bed reactor was used with a top feed method; reaction conditions: a volumetric space velocity of 1 h -1 , reaction temperature 25°C, reaction pressure 1.5MPa. The catalyst activity evaluation and stability test results are listed in Table 2 and Table 3 respectively.
[0065] Table 2 Evaluation results (sampling time: 10h)
[0066]
[0067]
[0068] Table 3 Stability evaluation (product thiol sulfur, μg / g)
[0069] Sampling time 48h 96h 144h 192h Example 1 <2 <2 4 8 Example 2 <2 <2 3 5 Example 3 <2 <2 2 4 Example 4 <2 <2 <2 2 Example 5 <2 <2 <2 <2 Example 6 <2 <2 <2 <2 Comparative Example 1 <2 <2 6 20 Comparative Example 2 <2 <2 11 50
Claims
1. A solid-supported alkali-free deodorization catalyst, characterized in that: The weight content includes: molecular sieve 35%-65%, xMO▪yM'2O3 10%-55%, and cobalt phthalocyanine 5%-25%; wherein M is a group ⅡA or group ⅡB element, M' is a group ⅢA or group Ⅷ element, and x:y=0.5~30.
2. The solid-supported alkali-free deodorization catalyst according to claim 1, characterized in that: M is at least one divalent metal selected from Mg, Ca, Ba, and Zn, and M' is at least one trivalent metal selected from Al, Fe, Co, and Ni.
3. The solid-supported alkali-free deodorization catalyst according to claim 1, characterized in that: The silicon to aluminum molar ratio of the molecular sieve is generally 0.5 to 200, preferably 1 to 50.
4. The solid-supported alkali-free deodorization catalyst according to claim 3, characterized in that: The molecular sieve is at least one selected from Y-type molecular sieve, X-type molecular sieve, MCM-41 molecular sieve, Al / MCM-48 molecular sieve, SBA-15 molecular sieve and the like.
5. The solid-supported alkali-free deodorization catalyst according to claim 1, characterized in that The catalyst comprises, by weight, 30%-75% of molecular sieve, preferably 40%-55%; 10%-55% of xMO▪yM'2O3, preferably 20%-35%; and 5%-25% of cobalt phthalocyanine, preferably 10%-20%.
6. The method for preparing the immobilized alkali-free deodorization catalyst according to any one of claims 1 to 5, comprising the following contents: (1) Preparation containing M 2+ and M' 3+ Add the molecular sieve into the mixed solution and stir evenly; (2) the material of step (1) and a mixed solution containing NaOH, Na2CO3 or a weak alkaline solution are simultaneously added dropwise to a reactor and reacted for a period of time under stirring; (3) The material obtained in step (2) is filtered, washed, dried and calcined to obtain a composite carrier; (4) Prepare a cobalt salt solution and transfer Co 2+ Exchange onto the composite carrier obtained in step (3); (5) The material obtained in step (4) is filtered and dried to obtain Co molecular sieve▪solid base; (6) The Co molecular sieve solid base obtained in step (5) is added to the pyridine and nitrobenzene mixture, and heated to 50-110°C under stirring; then phthalonitrile is added and reacted at 150-300°C; (7) The material obtained in step (6) is filtered, washed and dried to obtain the solid-supported alkali-free deodorization catalyst.
7. The preparation method according to claim 6, characterized in that: The stirring time in step (1) is 10 min-180 min.
8. The preparation method according to claim 6, characterized in that In the mixed solution of step (1), M is a Group IIA or Group IIB element, and M' is a Group IIIA or Group VIII element; preferably, M is at least one divalent metal selected from Mg, Ca, Ba, and Zn, and M' is at least one trivalent metal selected from Al, Fe, Co, and Ni.
9. The preparation method according to claim 6, characterized in that: The M-containing 2+ and M' 3+ The mixed solution is a nitrate solution or a hydrochloride solution of M and M', wherein the M 2+ and M' 3+ The concentrations of the mixed solutions were 0.1 mol / L-saturated concentration and 0.02 mol / L-saturated concentration; 2+ and M' 3+ The molar ratio is 0.5~30.
10. The preparation method according to claim 6, characterized in that: The M-containing 2+ and M' 3+ The molar ratio of NaOH to Na2CO3 in the mixed solution is 1:3-30:1; the weak alkali solution is selected from at least one of dilute ammonia water and dimethylamine.
11. The preparation method according to claim 6, characterized in that: When the pH value in step (2) is titrated to 9-10, stirring is stopped and the mixture is allowed to stand for 10-180 minutes.
12. The preparation method according to claim 6, characterized in that: The calcination conditions in step (3) are as follows: temperature of 400-900°C and calcination time of 4-10h.
13. The preparation method according to claim 6, characterized in that: The cobalt salt solution in step (4) is selected from at least one of Co(NO3)2, Co(AC)2 or CoCl2 solutions.
14. The preparation method according to claim 6, characterized in that: The operating conditions of the ion exchange in step (4) are: temperature is room temperature to 200°C, and the exchange time is 12 to 36 hours.
15. The preparation method according to claim 6, characterized in that: In the mixed solution described in step (6), the concentration of pyridine is 0.1-0.5 mol / L.
16. The preparation method according to claim 6, characterized in that: The heating temperature in step (6) is 50-110°C; after adding phthalonitrile, the reaction temperature is adjusted to 150-220°C and the reaction is continued for 0.5-3h.
Citation Information
Patent Citations
Solid catalyst for petroleum liquid component sweetening and preparation method
CN101474574A
Preparation method for phthalocyanine catalytic functional material with honeycomb structure
CN102302954A
Calcium alginate supported metal phthalocyanine microsphere catalytic material and preparation method thereof
CN104014371A
Preparation method for mercaptan oxidation catalyst
CN104588096A
Preparation method for mercaptan oxidation catalyst
CN104588097A
